Kinerja Pegawai Dalam Memberikan Pelayanan Publik pada Kantor Kecamatan Pineleng Kabupaten Minahasa - Lintjewas, Debby D.Y; Mamentu, Michael; Kawung, Evelin (JURNAL ILMIAH SOCIETY, 2016)
Subdistrict Pineleng entrance and exit for the flow of goods, people and traffic will be heading to Manado and Minahasa district to the capital. As the District that is located directly adjacent to the city of Manado where it is known as the capital of North Sulawesi province, thus requiring apparatus that has a high performance in providing public services. With high performance and good public services provided will be maximized. Therefore, the problem in this research is